2021
DOI: 10.1007/s00426-020-01471-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of observer’s gender, Body Mass Index and internalization of societal beauty ideals to visual body processing

Abstract: We examined whether visual processing mechanisms of the body of conspecifics are different in women and men and whether these rely on westernised socio-cultural ideals and body image concerns. Twenty-four women and 24 men performed a visual discrimination task of upright or inverted images of female or male bodies and faces (Experiment 1) and objects (Experiment 2). In Experiment 1, both groups of women and men showed comparable abilities in the discrimination of upright and inverted bodies and faces. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Several studies have shown that inversion also disrupts recognition of emotional expressions in faces (e.g., McKelvie, 1995;Prkachin, 2003;Bombari et al, 2013). Inversion effects have also been reported for bodies, for a range of judgments, including of body posture (Reed et al, 2003(Reed et al, , 2006, identity (Robbins & Coltheart, 2012;Cazzato, Walters, & Urgesi, 2021), size (Walsh, Vormberg, Hannaford, & Longo, 2018), attractiveness (Cook & Duchaine, 2011), and orientation (Bernard et al, 2012;Schmidt & Kistemaker, 2015). Of particular relevance here, body inversion effects have also been reported for emotional expressions, for stimuli including still photographs (Thoma et al, 2020), movies (Atkinson, Tunstall, & Dittrich, 2007;Zieber, Kangas, Hock, & Bhatt, 2014), and point-light displays (Dittrich, Troscianko, Lea, & Morgan, 1996;Clarke, Bradshaw, Field, Hampson, & Rose;Atkinson et al, 2007).…”
Section: Methodsmentioning
confidence: 53%
“…Several studies have shown that inversion also disrupts recognition of emotional expressions in faces (e.g., McKelvie, 1995;Prkachin, 2003;Bombari et al, 2013). Inversion effects have also been reported for bodies, for a range of judgments, including of body posture (Reed et al, 2003(Reed et al, , 2006, identity (Robbins & Coltheart, 2012;Cazzato, Walters, & Urgesi, 2021), size (Walsh, Vormberg, Hannaford, & Longo, 2018), attractiveness (Cook & Duchaine, 2011), and orientation (Bernard et al, 2012;Schmidt & Kistemaker, 2015). Of particular relevance here, body inversion effects have also been reported for emotional expressions, for stimuli including still photographs (Thoma et al, 2020), movies (Atkinson, Tunstall, & Dittrich, 2007;Zieber, Kangas, Hock, & Bhatt, 2014), and point-light displays (Dittrich, Troscianko, Lea, & Morgan, 1996;Clarke, Bradshaw, Field, Hampson, & Rose;Atkinson et al, 2007).…”
Section: Methodsmentioning
confidence: 53%
“…Taken together, these results may speak in favour of the hypothesis that a different engagement of local- vs. global-based processing is required to resolve self- to other-face discrimination, if one takes into account the two short and longer viewing times. For instance, several investigations using a face inversion task, according to which inverting a face can severely disrupt holistic, configural-based processing for faces [ 31 , 32 ], and consequently causing poor recognition, have shown that the processing of the own face relies on featural information [ 33 , 34 ]. Brédart [ 35 ] shows that while we rely mainly on configuration in recognizing others, local information is also important in recognizing ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…However, cautions have been raised such as the task being mirror reversal rather than visual processing of bodies [see 23 , 24 ]. More recently, Cazzato et al [ 25 ] found no effect of participant gender and found BIEs for both female and male stimuli, but with better processing of inverted male bodies. With the findings here, there are perhaps effects of embodiment or greater identification or perceptual sensitivity with participants focusing more on bodies of the same gender.…”
Section: Discussionmentioning
confidence: 99%